Pembukaan Prinsip Kerahasiaan Bank sebagai Perbuatan Melawan Hukum - Burhanudin Yusuf; Riana Puspita Sari; Rahelia Adisti Fransiska (Jurnal Syntax Admiration, 2023)
Banking secrecy is known in many countries in the world that have a bank financial institution. Banking secrecy is one of the most important principles. This is because one bank's development and growth are very dependent on public trust. Confidentiality of information that is born in banking activities is needed for the benefit of the bank and also the interest of the customer itself. This research discussed the function of the banking financial institution in protecting their customers through banking secrecy and the form of the tort of law against banking secrecy in judicial proceedings linked to the case. The method used in this research is juridical normative research. Data are collected by literature and document studies and then analyzed using descriptive qualitative analysis. The results of this research indicate that to overcome problems with banking secrecy, interference from the authorities in the consumer protection sector in the financial services field is needed that is, the Financial Services Authority institution, in Indonesian, is called Otoritas Jasa Keuangan. The institution is expected to be able to protect customers from financial service businesses that are considered to harm the interests of customers. In the case, the customer sued the bank for violating banking secrecy based on the tort of law that is contrary to the bank’s legal obligations and the law as referred to in Article 40 Paragraph 1 of the Banking Law.